Resolvemos problemas haciendo uso de las relaciones mayor, menor que e igual a, y comparamos números de 4 cifras - Rivera Rodríguez, Mirtha Elisa (2019)
The new national curriculum, stresses enough in maths subject. The methodology of the competence Approach of the problem solution, due to they are contextualized with the real-world learners live._x000D_ The learning session was designed for primary third grade, in the maths subject._x000D_ The learning session has as main goal to engage learners in searching of solution alternatives to the difficulty of the contextualized problems, making use of the symbols of comparison relation and ordering number of four digits.